2023
DOI: 10.3390/biomedicines11030917
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oxidative Stress Biomarkers with Risk Prognosis Values in Heart Failure

Abstract: Oxidative stress (OS) is mediated by reactive oxygen species (ROS), which in cardiovascular and other disease states, damage DNA, lipids, proteins, other cellular and extra-cellular components. OS is both initiated by, and triggers inflammation, cardiomyocyte apoptosis, matrix remodeling, myocardial fibrosis, and neurohumoral activation. These have been linked to the development of heart failure (HF). Circulating biomarkers generated by OS offer potential utility in patient management and therapeutic targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 215 publications
0
18
0
Order By: Relevance
“…DUOX, as a member of NADPH oxidase family, participated directly in generating hydrogen peroxide/ROS [ 29 ]. In normal condition, there is a balance between ROS and antioxidants, but the excessive amounts of ROS would result in various CVDs, including heart failure [ 4 ]. In this study, we found the increased DUOX1 expression levels in DOX-induced cellular heart failure model, suggesting that DUOX1 may contribute to heart failure development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DUOX, as a member of NADPH oxidase family, participated directly in generating hydrogen peroxide/ROS [ 29 ]. In normal condition, there is a balance between ROS and antioxidants, but the excessive amounts of ROS would result in various CVDs, including heart failure [ 4 ]. In this study, we found the increased DUOX1 expression levels in DOX-induced cellular heart failure model, suggesting that DUOX1 may contribute to heart failure development.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of DUOX1 in regulating heart failure has been also explored. It is well-known that heart failure development is associated with oxidative stress, which might be caused by the complex effects of ROS [ 4 ]. DUOX1-induced ROS production has also been shown in various diseases, such as DUOX1 nasal polyposis, allergy and asthma, chronic obstructive pulmonary disease, lung fibrosis and cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…163 Nitrotyrosine, a specific peroxynitrite-mediated protein modification, is also considered as a biomarker of protein oxidation. 178,182,183 Positive correlations have been reported between nitrotyrosine and human colorectal carcinoma, 184,185 prostate cancer 186 and gastric cancer. 187 Higher levels of nitrotyrosine were detected in H. pylori-infected gastric cancer patients than those without evidence of bacterium infection.…”
Section: Protein Damagementioning
confidence: 99%
“…Nitrotyrosine, a specific peroxynitrite‐mediated protein modification, is also considered as a biomarker of protein oxidation 178,182,183 . Positive correlations have been reported between nitrotyrosine and human colorectal carcinoma, 184,185 prostate cancer 186 and gastric cancer 187 .…”
Section: Host Damage and Gastric Cancermentioning
confidence: 99%